(untitled) (International Journal of Biology and Chemistry, 2025)
Over the past ten years, lithium-ion batteries (LIBs) have become indispensable for powering wearable technology, smart electronics, and electric cars. However, the use of extremely flammable and volatile liquid electrolytes in typical Li-ion rechargeable batteries raises serious safety issues and prevents future advancements in energy density and dependability. Solid electrolytes have been suggested as viable solutions to these problems. In particular, polymer-based solid electrolytes combine high ionic conductivity with advantages such as low flammability, mechanical flexibility, thermal stability, and improved safety. This review highlights recent advances in solid polymer electrolytes for LIBs, with a focus on their fabrication strategies, structural designs, ionic conductivities, and electrochemical/mechanical stabilities. Keywords: Lithium-ion batteries, Solid polymer electrolytes, Ionic conductivity, Safety, Electrochemical stability, Fabrication strategies.